Asymmetric synthesis of inositol derivatives - Patil, Nivedita T.; Sarkar, Nitai; Mysore, S. Shashidhar; Gonnade, Rajesh G. (Tetrahedron, 2024)
Both the enantiomers of racemic 4- O -tosyl-6- O -benzyl- myo -inositol-1,3,5-orthoformate ( 2 ) were isolated by preferential crystallization and used to synthesize several enantiomeric myo -inositol derivatives - natural ononitol, natural laminitol, precursors for myo -inositol phosphates and an oxabicyclo [2.2.1] heptane derivative. This work demonstrates the potential of the enantiomeric tosylates D2 and L2 to serve as versatile starting materials for the absolute asymmetric synthesis of inositol derivatives and other natural products from symmetric myo -inositol since no optically active molecular entity was required for the resolution of 2.
Keywords: Asymmetric synthesis; Carbohydrate; Cyclitol; Inositol; Natural product